Intrinsic and Extrinsic Aspects on Campylobacter jejuni Biofilms - Melo, Roberta T.; Mendonça, Eliane P.; Monteiro, Guilherme P.; Siqueira, Mariana C.; Pereira, Clara B.; Peres, Phelipe A. B. M.; Fernandez, Heriberto; Rossi, Daise A. (Frontiers in Microbiology, 2017)
Biofilm represents a way of life that allows greater survival of microorganisms in hostile habitats. Campylobacter jejuni is able to form biofilms in vitro and on surfaces at several points in the poultry production chain. Genetic determinants related to their formation are expressed differently between strains and external conditions are decisive in this respect. Our approach combines phylogenetic analysis and the presence of seven specific genes linked to biofilm formation in association with traditional microbiology techniques, using Mueller Hinton and chicken juice as substrates in order to quantify, classify, determine the composition and morphology of the biomass of simple and mixed biofilms of 30 C. jejuni strains. It also evaluates the inhibition of its formation by biocides commonly used in industry and also by zinc oxide nanoparticles. Genetic analysis showed high heterogeneity with the identification of 23 pulsotypes. Despite the diversity, the presence of flaA, cadF, luxS, dnaJ, htrA, cbrA, and sodB genes in all strains shows the high potential for biofilm formation. This ability was only expressed in chicken juice, where they presented phenotype of a strong biofilm producer, with a mean count of 7.37 log CFU/mL and an ultrastructure characteristic of mature biofilm. The composition of simple and mixed biofilms was predominantly composed by proteins. The exceptions were found in mixed biofilms with Pseudomonas aeruginosa, which includes a carbohydrate-rich matrix, lower ability to sessile form in chicken juice and compact architecture of the biofilm, this aspects are intrinsic to this species. Hypochlorite, chlorhexidine, and peracetic acid were more effective in controlling viable cells of C. jejuni in biofilm, but the existence of tolerant strains indicates exposure to sublethal concentrations and development of adaptation mechanisms. This study shows that in chicken juice C. jejuni presents greater potential in producing mature biofilms.